Influence of AlSi7Mg0.3 Alloy Modification on Corrosion Behaviour in the Salt Environment - Kusmierczak, Sylvia; Hren, Iryna (Manufacturing Technology Journal, 2019)
In the case of eutectic and hypoeutectic silumins, the modification is carried out on molten metal prior to casting with strontium, which has a limited modification effect of max. 1 - 1.5 hours. The aim of the realized experiment is to investigate the microstructure change and corrosion evaluation of the AlSi7Mg0.3 aluminium alloy in combination with the strontium modifier. AlSi7Mg0.3 alloy was used for the experiment using 0.04% strontium modifier and 0.15% beryllium was added to prolong the time effect of the strontium modification. Beryllium was used as an AlBe5 master alloy and the samples were cast by gravity casting into a metal preheated mold. Chemical composition analysis was performed by spectral analysis and microstructure was evaluated by light microscopy. Alloys formed without and after the addition of the modifier were subjected to a corrosion test followed by evaluation of the initial microstructure.
Keywords: aluminum alloys; modification; microstructure; corrosion test